DEVELOPMENT OF CARD-ASSISTED PATTAYA (SOLAR SYSTEM PUZZLE) LEARNING MEDIA AT SIXT GRADES SDN 30 CAKRANEGARA IN SCIENCE LEARNING - Ningsih, Ida Wahyu; Zain, Moh. Irawan; Rahmatih, Aisa Nikmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
Development of card-assisted PATAYA (Solar System Puzzle) learning media as an effort to provide innovation in science learning on solar system material. Innovations were made to overcome problems in science learning such as students being less active, teacher-centered learning, less varied use of media, and teachers having difficulty visualizing science material. The research aims to explain the design and determine the validity and practicality of the card-assisted PATAYA (Solar System Puzzle) learning media in Sisxt grades science learning at SDN 30 Cakranegara. The method used is Research and Development with a model developed by Sugiyono. The research results show that the development design using the Sugiyono model went through 9 stages, namely the potential & problem stage, data collection, product design, design validation, design revision, product testing, product revision, usage testing, and product revision. The results of the media validity test are in the very valid category based on the assessment of media experts at 98.75% and material experts at 86%. The level of practicality of the media is in the very practical category based on the teacher's response assessment at the two testing stages of 100%, while the student response assessment at the product trial was 96.59% and the usage trial stage was 97.63%. Through these results, it can be concluded that the card-assisted PATAYA (Solar System Puzzle) learning media can be used in Sisxt grades science learning at SDN 30 Cakranegara. This research has implications for the science learning process which makes it easier for teachers to explain the solar system material to students and can foster student activity.